Aktivitas Antioksidan Ekstrak Biji Duwet (Syzygium cumini Linn.) pada Peroksidasi Lipida Secara In Vitro - Rohadi Rohadi; Sri Rahadjo; Iip Izul Falah; Umar Santoso (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2016)
All parts of Syzygium cumini Linn. (duwet) were widely used for medicinal plant in the treatment of various deseases. The seed extract was used to lower blood glucose. Cumini's seed had higher phenolic fractions than others. It were prepared by extracted of duwet seed